Mechanism and kinetics of electrochemical degradation of uric acid using conductive-diamond anodes. Issue 23 (1st December 2016) - Dbira, Sondos; Bensalah, Nasr; Bedoui, Ahmed
ABSTRACT: Uric acid (UA) is one of the principal effluents of urine wastewaters, widely used in agriculture as fertilizer, which is potentially dangerous and biorefractory. Hence, the degradation of UA (2, 6, 8-trihydroxy purine) in aqueous solution of pH 3.0 has been studied by conductive-diamond electrochemical oxidation. Hydroxyl radicals formed from water oxidation at the surface of boron-doped diamond anodes were the main oxidizing agents. Effects of current density and supporting electrolyte on the degradation rate and process efficiency are assessed. Results show that the increase of current density from 20 to 60 mA cm –2 leads to a decrease in the efficiency of the electrochemical process. In addition, the best degradation occurred in the presence of NaCl as conductive electrolyte. Interestingly, an almost total mineralization of 50 ppm UA was obtained when anodic oxidation was performed at low current densities (20 mA cm –2 ) and in the presence of NaCl. This result confirmed that the electrolysis using diamond anodes is a very interesting technology for the treatment of UA. The identification of UA transformation products was performed by high-performance liquid chromatography (HPLC). HPLC analysis of treated solutions revealed that oxalic acid and urea were the two intermediates found. Oxalic acid was the most persistent product. Based on detected intermediates and bibliographic research, a mechanism of UA mineralization by anodic oxidation has been proposed. Ionic chromatography analysis confirmed the release of and ions during UA mineralization.